Empirical Brightness Control and Equalization of Mars Context Camera Images. Issue 10 (23rd October 2020) - Robbins, Stuart J.; Kirchoff, Michelle R.; Hoover, Rachael H.
Abstract: The Mars Reconnaissance Orbiter ( MRO ) spacecraft has been in orbit around Mars since March 2006. The Context Camera (CTX) on MRO has returned over 115, 000 images of the planet at approximately 5–6 m per pixel, providing nearly global coverage. During that time, Mars has gone through nearly seven of its own years, changing solar distance from 1.38 to 1.67 AU and the corresponding solar flux by 45% due to its orbital eccentricity. Seasonal effects and transient phenomena affect atmospheric transparency. These changes, along with an aging detector, prevent easily equalizing images to create a visually smoothly illuminated product from CTX images. We have developed a method, based on previous work by other researchers for other data sets, to mitigate almost all brightness variations between images in order to create the appearance of an evenly illuminated, practically seamless mosaic. We describe how the process works, which uses a reference source to tie brightness values, and demonstrate its effects across Mars' surface. While the workflow developed for this product is applicable to other planetary bodies, it requires a reference source, which may not yet exist. Plain Language Summary: Creating a mosaic of images of planetary surfaces is relatively straightforward in theory: Geometric data of the camera and spacecraft tell us where and how images should be placed relative to each other. A process which can be more challenging is matching brightness variations across the images to create a mosaic that appears seamless. Different mathematical mechanisms exist to try to adjust brightness and contrast of overlapping images to match, but this is not always possible. For example, if two overlapping images were taken when the sun was in different locations in the sky, then it will be impossible to get the shadows to match. If clouds or a dust storm dims an image and reduces contrast, it will be hard to match to another that was taken when the atmosphere was clear. In this work, we present a more advanced method to create the appearance of a seamless mosaic. We achieve this by not matching images to each other, but to a coarser, lower‐resolution reference that already has even illumination. We tailored our application to the Context Camera that has been returning ≈6 m per pixel images of Mars since 2006, and we demonstrate it across different terrains of Mars. Key Points: We provide the first broad‐scale application of empirical brightness control to Context Camera data from the Mars Reconnaissance Orbiter The resulting mosaics are nearly seamless when images are relatively consistent The accuracy of brightness control depends on accuracy of a reference source and factors such as similar solar illumination